1999
DOI: 10.1136/hrt.81.3.323
|View full text |Cite
|
Sign up to set email alerts
|

ECG diagnosis of native heart ventricular tachycardia in a heterotopic heart transplant recipient

Abstract: A case is reported of haemodynamic collapse in a 51 year old male heterotopic heart transplant recipient caused by native heart ventricular tachycardia. An accurate diagnosis was made by selective right and left sided electrocardiography. Synchronised electrical cardioversion of the native heart (200 J) resulted in restoration of sinus rhythm with prompt relief of symptoms and amelioration of the clinical situation. (Heart 1999;81:323-324) Keywords: transplantation; ventricular tachycardia A 51 year old man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 3 publications
0
6
0
Order By: Relevance
“…To date, with the improvements in immunosuppressive therapy, it is generally reserved to a specific subset of conditions such as donor scarcity, difficulties in matching sizes (major donor-recipient body-size mismatch >30%) [3] or in patients suffering from severe pulmonary hypertension. In this setting, in fact, orthotopic heart transplantation is generally denied since the thin walled right ventricle of the donor heart will not be able to sustain the sudden increase in the right ventricular afterload imposed by the high pulmonary circulation pressure [4].…”
Section: Discussionmentioning
confidence: 99%
“…To date, with the improvements in immunosuppressive therapy, it is generally reserved to a specific subset of conditions such as donor scarcity, difficulties in matching sizes (major donor-recipient body-size mismatch >30%) [3] or in patients suffering from severe pulmonary hypertension. In this setting, in fact, orthotopic heart transplantation is generally denied since the thin walled right ventricle of the donor heart will not be able to sustain the sudden increase in the right ventricular afterload imposed by the high pulmonary circulation pressure [4].…”
Section: Discussionmentioning
confidence: 99%
“…The standard ECG shows the native heart better, while right modified leads give information about the donor heart [2,3]. It is possible that only one of the two hearts (most frequently the native one) has serious arrhythmias [4][5][6].…”
Section: Discussionmentioning
confidence: 99%
“…This case report brings information regarding ablation of VT after heterotopic HT. First, as mentioned in previous reports, 4–6 it is important to identify which heart is a source of VT. In the present case, surface ECG suggested that VT originated from the recipient heart.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, various arrhythmias may occur after both types of surgery. While most of the previous reports dealt with supraventricular tachycardias after orthotopic HT, few mentioned arrhythmias following heterotopic HT 1–6 . To the best of our knowledge, ablation of ventricular tachycardia (VT) from the recipient heart after heterotopic HT has not been published.…”
Section: Introductionmentioning
confidence: 99%